KESIAPAN PUSTAKAWAN DI ERA TEKNOLOGI INFORMASI - Armen Armen (UIN Imam Bonjol Padang, 2019)
This study aims to explain and to know the competencies, efforts, challenges and oppurtunities of librarian for enconnter the profeccion information tecnology. The type of study data is qualitative with literature review as data sources. The literature that has been reviewed then analyzed based on the subject matter. The Ressuts of this study indicate that librarians (in various types of library institutons) schould improve their competences and conduct the library transpormations to distruption prepation. Librarians need to increase their profeccional comptence in terms of library e-resouces management, managerial leadhersip, digital literacy, and risearch literacy. These competecies as the librarian asset at transform the library and realize the knowlegdeable community. In adittion. Librarians must look at disruption issue and phenomena as positive challenges and opportunities for professional carrer development n the future. As the recomedation, librarian need to keep up of informations tecnology, nomely knowlegde strengthening, connectivity bulding, and oriented to the comunnity needs. This is done sho thad librarians are ready to acounter the disruption and library services provided to users.